Numerical modelling of fluid transportation based on digital core model. (October 2019) - Liu, Jianjun; Wang, Rui; Zhang, Bohu; Zu, Lin; He, Xiang
Abstract: Rock pore is the storage space and migration channel of geo-fluid resource like petroleum, coalbed methane and shale gas etc. In this paper, the rock core microscopic pore structure based on CT image is studied through image processing. Then the parameters are analyzed statistically by numerical modelling. The reconstructed software Mimics is used to reconstruct the core structural model. Finally, the relationship between the pore structure parameters and penetrability is studied by numerical simulation. The equivalent permeability of the reconstructed core is calculated by using FEM software Abaqus. The results shown that fluid percolation is directly related with porosity, pore shape, pore conectivity. The permeability of core can be obtained by substituting flow numerical simulation for seepage laboratory experiment.